2022
DOI: 10.3389/fpsyt.2022.1038122
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of palmitoylethanolamide in cognitive decline: A systematic review and preliminary meta-analysis of preclinical and clinical evidence

Abstract: Cognitive decline is believed to be associated with neurodegenerative processes involving excitotoxicity, oxidative damage, inflammation, and microvascular and blood-brain barrier dysfunction. Interestingly, research evidence suggests upregulated synthesis of lipid signaling molecules as an endogenous attempt to contrast such neurodegeneration-related pathophysiological mechanisms, restore homeostatic balance, and prevent further damage. Among these naturally occurring molecules, palmitoylethanolamide (PEA) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Moreover, our observations support prior research examining the effects of various anti-inflammatory nutraceuticals on BDNF levels. Investigations into anti-inflammatory compounds such as curcumin [ 51 ], zinc [ 52 ], probiotics [ 53 ], polyphenols [ 54 ], and carotenoids [ 55 ] have provided valuable insights into the potential influence of diverse dietary interventions on BDNF. A systematic review of 48 recent human interventions has reported mixed outcomes on BDNF concentrations for the various dietary interventions [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our observations support prior research examining the effects of various anti-inflammatory nutraceuticals on BDNF levels. Investigations into anti-inflammatory compounds such as curcumin [ 51 ], zinc [ 52 ], probiotics [ 53 ], polyphenols [ 54 ], and carotenoids [ 55 ] have provided valuable insights into the potential influence of diverse dietary interventions on BDNF. A systematic review of 48 recent human interventions has reported mixed outcomes on BDNF concentrations for the various dietary interventions [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first systematic review of all evidence exploring the biobehavioral correlates of palmitoylethanolamide (PEA) in psychosis across human and animal studies. Unlike previous research in this field ( 38 40 ), the greatest majority of records included consisted of human studies. Existing reviews focusing on the role of the major phytocannabinoid cannabidiol (CBD) as a potential treatment for schizophrenia (SCZ) patients ( 20 , 56 , 57 ) gathered still preliminary evidence supporting its antipsychotic (AP) efficacy, while highlighting its advantageous side effect profile and good tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of neuroinflammation has been identified in the advancement of different types of dementia [5,60]. A clinical study has suggested that the supplementation of PEA could provide advantages in the context of disorders connected to dementia [60]. This research has documented enhancements in cognitive performance and a decrease in neuroinflammation among persons diagnosed with vascular dementia and Alzheimer's disease.…”
Section: Dementiamentioning
confidence: 99%
“…Dementia represents a substantial worldwide health concern due to its manifestation of cognitive deterioration and memory impairment. The involvement of neuroinflammation has been identified in the advancement of different types of dementia [5,60]. A clinical study has suggested that the supplementation of PEA could provide advantages in the context of disorders connected to dementia [60].…”
Section: Dementiamentioning
confidence: 99%